The Influence of Marketing Content and Brand Image on Vespa Coffee (KOPVES) Purchase Decisions - Riza Ardy Saputra; Siska Ernawati Fatimah (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study was conducted to analyze